Choose to fly higher rather than pacing around. Issue 4 (11th March 2020) - Musumeci, Giuseppe; Aranzulla, Tiziana Claudia
Key Points: Pre‐existing right bundle branch block and the depth of the prosthesis in the left ventricle are predictors of permanent pacemaker implantation (PPI) following transcatheter aortic valve replacement. The recapturable capability of the Evolut R system allows higher and more precise valve implantation and this was associated with halved incidence of PPI as compared with the CoreValve. Larger studies are needed to assess the feasibility of systematic very high implantation (depth in the left ventricle outflow tract ≤3 mm) of the Evolut R and the associated rate of PPI.